The Environment in Andalusian Critical Discourse: An Analytical Study - Ahmed, Dr.Wesam Mahdi (Thi Qar Arts Journal, 2025)
The research is devoted to exploring the criterion of environment in the Andalusian critical corpus and uncovering the extent of its dominance in shaping creative discourse. These texts, regarded as enduring legacies of their people, stand out as a hidden treasure that continues to offer its creative masterpieces, within which is embedded the intellectual and cultural history of Andalusian society.    In addition, the study investigates the intertwined and interconnected relationship of the visions and ideas inspired by the environment in expressing critical positions, together with the ways in which natural elements were employed and subjected to critical examination.